2018
DOI: 10.1097/dss.0000000000001453
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Clinical Changes in Vulvovaginal Tissue After Treatment With a Transcutaneous Temperature-Controlled Radiofrequency Device

Abstract: Transcutaneous temperature-controlled RF resulted in significant improvements in AV, VVL, and sexual satisfaction with milder improvements in OD and SUI. Post-treatment histology demonstrated neocollagenesis, neoelastogenesis, neoangiogenesis, and the first reported finding of TTCRF-related neurogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…The term VLS and therefore its therapy, vaginal rejuvenation, is not endorsed or formally defined by the leading gynecological societies . However, management of the symptoms have evolved from techniques involving sutures and the adaptation of traditional urogynecological procedures to the use of LASER and radiofrequency procedures …”
Section: Vaginal Laxity Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…The term VLS and therefore its therapy, vaginal rejuvenation, is not endorsed or formally defined by the leading gynecological societies . However, management of the symptoms have evolved from techniques involving sutures and the adaptation of traditional urogynecological procedures to the use of LASER and radiofrequency procedures …”
Section: Vaginal Laxity Syndromementioning
confidence: 99%
“…11 However, management of the symptoms have evolved from techniques involving sutures and the adaptation of traditional urogynecological procedures to the use of LASER 61,90 and radiofrequency procedures. [91][92][93][94][95][96][97][98][99] In 2011, there was an attempt to restore the rugae of the vagina in postmenopausal women ("vaginal rugation rejuvenation"), by vaporization of the vaginal wall in order to create parallel grooves. The procedure was performed in women with a sensation of a loose or smooth vagina.…”
Section: Grade Of Recommendationmentioning
confidence: 99%
“…Several studies using radiofrequency devices for GSM have demonstrated evidence of benefit; however, these are small observational studies. As with laser treatment, there appears to be a greater improvement in GSM than in SUI or sexual dysfunction …”
Section: Indications and Evidence For Usementioning
confidence: 99%
“…As with laser treatment, there appears to be a greater improvement in GSM than in SUI or sexual dysfunction. 29…”
Section: Radiofrequency Devicesmentioning
confidence: 99%
“…The term VLS, and therefore its therapy, vaginal rejuvenation, is not endorsed or formally defined by the leading gynecological societies 11 . However, management of the symptoms have evolved from techniques involving sutures and the adaptation of traditional urogynecological procedures to the use of LASER 61,89 and radiofrequency procedures [90][91][92][93][94][95][96][97][98] .…”
Section: Impact On the Vaginal Microbiomementioning
confidence: 99%